2021
DOI: 10.1093/bjs/znab376
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open resection of hepatocellular carcinoma in patients with cirrhosis: meta-analysis

Abstract: Background The exact role of laparoscopic liver resection (LLR) in patients with hepatocellular carcinoma (HCC) and underlying liver cirrhosis (LC) is not well defined. In this meta-analysis, both long- and short-term outcomes following LLR versus open liver resection (OLR) were analysed. Methods PubMed, EMBASE, Scopus and Web of Science databases were searched systematically for randomised controlled trials (RCTs) and propen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…Compared to open liver resection (OLR), LLR has led to less postoperative pain, complications, and shorter postoperative hospital stays although the overall recurrence rate and survival rate were not significantly different between the two groups. [322][323][324] With the development of laparoscopic techniques and surgical instruments, especially laparoscopic imaging system (4K, 3D, and indocyanine green fluorescence images), major hepatectomy, hepatectomy for recurrent HCC, hepatectomy for HCC in patients with liver dysfunction have also gradually increased. [325][326][327] A recent study showed that compared to OLR, LLR for patients with Child-Pugh B7 cirrhosis or portal hypertension was associated with less perioperative bleeding, postoperative pain, complications, and shorter postoperative hospital stays.…”
Section: Basic Principles Of Hepatic Resectionmentioning
confidence: 99%
“…Compared to open liver resection (OLR), LLR has led to less postoperative pain, complications, and shorter postoperative hospital stays although the overall recurrence rate and survival rate were not significantly different between the two groups. [322][323][324] With the development of laparoscopic techniques and surgical instruments, especially laparoscopic imaging system (4K, 3D, and indocyanine green fluorescence images), major hepatectomy, hepatectomy for recurrent HCC, hepatectomy for HCC in patients with liver dysfunction have also gradually increased. [325][326][327] A recent study showed that compared to OLR, LLR for patients with Child-Pugh B7 cirrhosis or portal hypertension was associated with less perioperative bleeding, postoperative pain, complications, and shorter postoperative hospital stays.…”
Section: Basic Principles Of Hepatic Resectionmentioning
confidence: 99%
“…Another factor affecting the difficulty of LLR and therefore L-CLR is the presence of liver cirrhosis. [38][39] Cirrhotic livers have significantly enlarged caudate lobes compared to a non-cirrhotic liver. The enlarged and fibrotic caudate lobe will therefore be harder to manipulate and dissect off the IVC, biliary confluence and hepatic inflow.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor affecting the difficulty of LLR and therefore L‐CLR is the presence of liver cirrhosis 38–39 . Cirrhotic livers have significantly enlarged caudate lobes compared to a non‐cirrhotic liver.…”
Section: Discussionmentioning
confidence: 99%
“…From our experience, lymphadenectomy in particular is more easily performed when using the robotic approach. Furthermore, positive impact may be inferred based on data on robotic liver resection for other entities [ 63 , 64 ]. Taken together, the minimally invasive approach is supported in guidelines and consensus statements as the preferred technical approach for liver resection whenever technically feasible [ 65 , 66 ].…”
Section: Liver Resectionmentioning
confidence: 99%